Near zero fluoroscopy in cryoballoon catheter ablation in patients with atrial fibrillation using the new KODEX-EPD imaging system. (24th May 2021) - Schillaci, V; Stabile, G; Arestia, A; Shopova, G; Solimene, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Fluoroscopy is commonly used in cryoballoon catheter ablation for pulmonary vein (PV) isolation procedures in patients with atrial fibrillation (AF). Objective The purpose of this study was to verify the feasibility of a new dielectric imaging system in reducing the radiation exposure during cryoballoon ablation in patients with AF. Methods We enrolled 26 consecutive patients with paroxysmal AF: 13 patients underwent the procedure under fluoroscopy guidance before the new system introduction, while 13 patient underwent the procedure under fluoroscopy and KODEX-EPD system guidance with its occlusion tool software. After transseptal access a detailed image reconstruction of left atrium and PVs was achieved with the Achieve octapolar circular mapping catheter and the cryoablation was performed with the Arctic Front Advance cryoballoon. Results Total time of the procedure was comparable between the two groups (90.15 ± 28.67 vs 80.77 ± 17.17 using KODEX-EPD, p = 0.34), while fluoroscopy time was significantly lower in the group using KODEX-EPD (16.92 ± 8.96 vs 5.54 ± 2.06, p < 0.01). Acute isolation was achieved in all PVs. No 30 days complication was observed. Conclusion This is the first study that demonstrates the feasibility of a reduce fluoroscopy workflow using the novel KODEX-EPD system in a cryoballoon procedure.